Paleoecology of a Late Pleistocene Small Mammal Community from Interior Alaska - Guthrie, R.D. (ARCTIC, 1968)
The material was recovered from exposures, mostly mine cuts through the silt, to reach auriferous gravels at five localities near Fairbanks. The age range of the silts is mainly early Illinoian - present. The vole Microtus gregalis predominates in the fossil assemblage, indicating a habitat above tree line with welldrained soils. M. gregalis, Citellus undulatus and Dicrostonyx torquatus are not now found in the area however, and their extinction is attributed to a rapid reduction of a preferred habitat at the end of the Wisconsin glaciation. Evidence from large mammalian fossils indicates that tree line was lowered at least 300 m during the Wisconsin phase and that most of the mammals were grazers. This supports the small mammalian indications that welldrained alpine meadow expanded almost down to the river flats in interior Alaska during the last two glaciations. The distribution changes and extinction of the small mammals are discussed in relation to the intercontinental communities and interchanges within the Beringian refugium in eastern Siberia and Alaska. Paléoécologie d'un Petit Groupe de Mammifières du Pléistocène Récent de l'Intérieur de l'Alaska. De petits mammifères fossiles des sédiments du Pléistocène récent de l'Alaska intérieur ont servi à l'étude de la paléoécologie de cette région. L'élément dominant de cet assemblage fossile était Microtus gregalis, ce qui indiquerait que la région se trouvait au nord de la limite de la zone forestière et que la faune et la flore qui l'occupaient préféraient les sols bien drainés. Trois espèces fossiles sont maintents absentes de la région: Microtus gregalis, Citellus undulatus et Dicrostonyx torquatus. Leur extinction dans l'Alaska intérieur semble due à une régression rapide de leur habitat préféré, vers la fin de la glaciation wisconsinienne. Cette interprétation écologique du paléogroupe et de son extinction corcorde avec les interprétations que suggèrent les assemblages fossiles de grands mammifères de la même région.